Boosting Performance through Contingen Incentives: The Mediation Effect Of Organizational Commitment - Alfiany Alim Imro'ah (Universitas Bangka Belitung, 2026)
This study examines the effect of types of incentive schemes on performance mediated by organizational commitment. This research aims to expand the investigation regarding the factors that may influence performance, as well as the impact of different incentive schemes on performance by incorporating the mediating variable of organizational commitment, which is believed to have a positive effect on individual performance. To achieve that goal, the research method used in this study is the experimental method. This research uses laboratory experiments. The participants are undergraduate students majoring in Accounting from the Faculty of Economics and Business at Ahmad Dahlan University Yogyakarta who have completed or are currently taking Management Accounting courses. This study predicts that the quota incentive scheme results higher performance and commitment organizational than the piece rate incentive scheme. This study also predicts that the type of incentive scheme affects performance through organizational commitment. The test results of 54 participants showed that the quota incentive scheme resulted higher organizational performance and commitment than the piece rate incentive scheme. This research also found that organizational commitment influences performance. However, this study did not find evidence that organizational commitment mediates the effect of the type of incentive scheme on performance. Therefore, a deeper theoretical study is still needed regarding organizational commitment as a mediating variable in the relationship between types of incentive schemes and employee performance.